2017
DOI: 10.1167/iovs.17-21826
|View full text |Cite
|
Sign up to set email alerts
|

KLF4 Plays an Essential Role in Corneal Epithelial Homeostasis by Promoting Epithelial Cell Fate and Suppressing Epithelial–Mesenchymal Transition

Abstract: PurposeThe purpose of this study was to test the hypothesis that KLF4 promotes corneal epithelial (CE) cell fate by suppressing the epithelial–mesenchymal transition (EMT), using spatiotemporally regulated CE-specific ablation of Klf4 in Klf4Δ/ΔCE (Klf4LoxP/LoxP/Krt12rtTA/rtTA/Tet-O-Cre) mice.MethodsCE-specific ablation of Klf4 was achieved by feeding Klf4Δ/ΔCE mice with doxycycline chow. The wild-type (WT; normal chow-fed littermates) and the Klf4Δ/ΔCE histology was compared by hematoxylin and eosin–stained s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(75 citation statements)
references
References 83 publications
(134 reference statements)
6
68
1
Order By: Relevance
“…Apicobasal polarity is disrupted in Klf4 Δ/ΔCE CE. As reported previously (14,17,19,20), CEspecific ablation of Klf4 resulted in hyperplasia concurrent with downregulation of CE markers keratin-12 (Krt12), tight junction protein-1 (Tjp1), and E-cadherin, reminiscent of EMT (Supplemental Fig. 1).…”
Section: Resultssupporting
confidence: 71%
See 4 more Smart Citations
“…Apicobasal polarity is disrupted in Klf4 Δ/ΔCE CE. As reported previously (14,17,19,20), CEspecific ablation of Klf4 resulted in hyperplasia concurrent with downregulation of CE markers keratin-12 (Krt12), tight junction protein-1 (Tjp1), and E-cadherin, reminiscent of EMT (Supplemental Fig. 1).…”
Section: Resultssupporting
confidence: 71%
“…Previously, we reported that CE-specific ablation of Klf4 results in (i) EMT coupled with loss of CE barrier function and hyperplasia (14,17,20), and (ii) activation of canonical TGF-KLF4, corneal epithelial polarity and plane of division β signaling and downregulation of cell cycle inhibitors favoring increased proliferation (21). The data presented in this report elucidate the crucial role of Klf4 in orchestrating the CE stratification and homeostasis by coordinating the expression and localization of ABP determinants, and plane of CE cell division ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations